Aspterpenacids A and B, Two Sesterterpenoids from a Mangrove Endophytic Fungus Aspergillus terreus H010 - Liu, Zhaoming; Chen, Yan; Chen, Senhua; Liu, Yayue; Lu, Yongjun; Chen, Dongni; Lin, Yongcheng; Huang, Xishan; She, Zhigang (Organic letters, 2016)
Two new sesterterpenoids, aspterpenacids A (1) and B (2), with an unusual carbon skeleton of a 5/3/7/6/5 ring system were isolated from the mangrove endophytic fungus Aspergillus terreus H010. Their structures were elucidated on the basis of spectroscopic methods, single-crystal X-ray diffraction analysis, and electronic circular dichroism calculations. A biogenetic pathway for 1 and 2 is proposed. Both 1 and 2 showed no significant antibacterial activity or cytotoxicity at 50 μM.